Early Clinical Outcome of Limb Salvage Surgery of Osteosarcoma in the Lower Extremity Using Liquid Nitrogen - Primadika Rubiansyah; Muhammad Randi Akbar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Osteosarcoma in the lower extremity has become a challenge for orthopedic surgeons to manage because surgeons need to preserve the affected joint's functions and retain stability as physiologic as possible. Thus, limb salvage surgery may be the treatment of choice. One of the techniques using liquid nitrogen provides better functionality and efficacy in preventing recurrence. Methods. From October 2020 to October 2021, 7 patients with primary musculoskeletal sarcoma underwent limb salvage surgery (LSS) by wide resection of the tumor and reconstruction using recycled Autograft treated with liquid nitrogen. The resected bone was dipped in liquid nitrogen for 15 min and thawed at room temperature for 15 min. The recycled bone was re-implanted into its original site and stabilized with internal fixation, and some of them followed with arthroplasty. Results. Average age was 14.14 years old. The most common site was the distal femur which was found in 3 cases (42,8%). During the 6-months-follow-up period, all patients had a good function (mean functional MSTS score of 90%) with one case of local recurrence in the re-implanted bone and one case of infection. No metastasis was reported in any patient. Conclusion. Satisfying functional results were recorded in all subjects treated with cryosurgery in Dr. Mohammad Hoesin General Hospital Palembang with equal results with studies around the world.